EXPLORING SEVENTH GRADE STUDENTS’ PERCEPTIONS OF READING STRATEGIES IN ENGLISH READING - Ni’mah, Fauziyatun; Rahayu, Anita Budi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The problem of low English reading comprehension among EFL students at the junior secondary school level highlights the importance of using effective reading strategies in learning. This study focuses on seventh-grade students’ perceptions of reading strategies in English learning at MTs Nurul Huda Grogol Masangan and employed a qualitative descriptive design involving 35 students. Data were collected through open-ended questionnaires and semi-structured interviews and were analyzed descriptively and thematically to ensure depth and credibility of findings. The findings indicate that students predominantly used cognitive reading strategies, such as identifying main ideas, guessing word meanings from context, rereading difficult parts of the text, and relating the text to prior knowledge, which were perceived as helpful in improving reading comprehension. However, the study also revealed major challenges, including limited vocabulary mastery, low reading confidence, and students’ difficulties in applying reading strategies independently without teacher guidance. In addition, a gap was identified between the reading strategies taught by teachers and those consistently practiced by students during classroom activities. Therefore, this study concludes that explicit and structured instruction in reading strategies is necessary to bridge this gap and to improve the quality of English reading instruction in similar school contexts. ABSTRAK Masalah rendahnya pemahaman membaca bahasa Inggris pada siswa EFL di tingkat sekolah menengah pertama menunjukkan pentingnya penggunaan strategi membaca yang efektif dalam pembelajaran. Penelitian ini berfokus pada persepsi siswa kelas VII terhadap strategi membaca dalam pembelajaran bahasa Inggris di MTs Nurul Huda Grogol Masangan dengan menggunakan desain kualitatif deskriptif yang melibatkan 35 siswa. Data dikumpulkan melalui kuesioner terbuka dan wawancara semi terstruktur, kemudian dianalisis secara deskriptif dan tematik. Hasil penelitian menunjukkan bahwa siswa lebih dominan menggunakan strategi membaca kognitif, seperti mengidentifikasi ide pokok, menebak makna kosakata berdasarkan konteks, membaca ulang bagian teks yang sulit, serta mengaitkan isi teks dengan pengetahuan sebelumnya, yang dipersepsikan membantu meningkatkan pemahaman membaca. Namun, penelitian ini juga mengungkap permasalahan utama berupa keterbatasan penguasaan kosakata, rendahnya kepercayaan diri dalam membaca, serta kesulitan siswa dalam menerapkan strategi membaca secara mandiri tanpa bimbingan guru. Selain itu, ditemukan adanya kesenjangan antara strategi membaca yang diajarkan oleh guru dan strategi yang secara konsisten dipraktikkan oleh siswa dalam kegiatan pembelajaran. Oleh karena itu, penelitian ini menyimpulkan bahwa pengajaran strategi membaca yang eksplisit dan terstruktur diperlukan untuk menjembatani kesenjangan tersebut serta meningkatkan kualitas pembelajaran membaca bahasa Inggris pada konteks sekolah yang serupa.